Science fiction's eugenic dreams : a look into American popular culture and genetic manipulation in the 1980s to 1990s - Ong, Hannah Xue Wen (Nanyang Technological University, 2021)
Eugenics has always been a controversial biosocial and political topic. During the 1980s and 1990s, the development of genetic technology or projects caused fear of eugenics in Americans. The Human Genome Project of the 1990s is a key example which fueled anxieties in many. In this paper, I intend to explore a different aspect of eugenics – that is, within American popular culture. I argue that while people were cautious of eugenics, they were often fascinated by eugenic themes and storylines in American popular culture. While some forms of popular culture and eugenics incited fear, most instead sparked fascination and a following. Therefore, my thesis is that despite the fearful times of the 1980s to 1990s, Americans still enjoyed American popular culture that explored eugenic themes.